Hepatobiliary Brucellosis: Brucella Bacteremia Presenting with Refractory Hepatobiliary Infection - Dania El Hallak; Mae Al Habbal; Wael Hassan Zorkot (Case Reports in Critical Care)
Brucellosis often presents with common and nonspecific symptoms such as fever, malaise, and arthralgia but can also involve primary organs. Intra-abdominal involvement is rare. We report a case of hepatobiliary brucellosis presenting as a refractory hepatobiliary infection in a healthy young adult with no underlying rheumatologic disease or history of exposure to risk factors. Detection of Brucella in the blood led to a shift in the patient’s management and consequently her recovery.